Struktur Populasi Keong Murbei Pomacea Spp. (Mesogastropoda : Ampullariidae) Pada Tanaman Padi Sawah di Kabupaten Jembrana Provinsi Bali - I PUTU DEDI ADNYANA; I WAYAN SUPARTHA; I MADE MEGA ADNYANA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Population Structure of Murbei Conch Pomacea spp. (Mesogastropoda: Ampullariidae) On Paddy Rice Field in Jembrana District of Bali Province The purpose of this study is to determine the population structure of mulberry snails. This research was carried out in October 2017 - March 2018. The method used in this study was a survey method with a diagonal model. Biological parameters are carried out by randomly taking egg groups and maintaining them in the Integrated Pest and Disease Laboratory, Faculty of Agriculture, Udayana University. The results showed that the population density of P. canalicuta in the group of eggs and conch with a size (0.5-1cm), (> 1-2.5cm), (> 2.5-4cm) higher in Subak Pangyangan and lower in Subak Tegalwani. Distribution of P. canaliculata in Tegal Wani Subak and Pangyagan Subak has a groups pattern. The age structure of P. canaliculata in Subak Tegal Wani and Subak Pangyangan from egg groups aged 7-14 days, (0.5-1 cm) aged 15-25 days, (> 1 - 2.5 cm) aged 26-49 days, (> 2.5 - 4 cm) 50-60 days old. The highest peak of the population development of P. canalicuta in Subak Tegal Wani occurs at the age of the plant 8 weeks after planting, while the highest peak in Subak Pangyangan occurs at the age of the plant 6 weeks after planting.